PTFI: Access and benefit sharing protocols and procedures guide - Reep, Alexandra Dumaine; Khoury, Colin Kahlil; Neira-Monsalve, Esteban; Riddle Lee, Katie; Lago Candeira, Alejandro Francisco; Rouard, Mathieu; Lopez Noriega, Isabel; Brinkley, Sarah Christine (American Heart Association, 2025)
Promoting Ethical and Legal Data Stewardship through Access and Benefit Sharing (ABS): Central to the PTFI’s mission is a commitment to support ethical and legal data stewardship, in addition to the equitable sharing of benefits from the utilization of Digital Sequence Information (DSI) derived from genetic resources and associated traditional knowledge. This commitment aligns with international agreements such as the Nagoya Protocol1 and DSI instruments under the Convention on Biological Diversity (CBD).